2020
DOI: 10.1007/s00198-020-05714-4
|View full text |Cite
|
Sign up to set email alerts
|

High-impact exercise stimulated localised adaptation of microarchitecture across distal tibia in postmenopausal women

Abstract: We provided evidence that a 6-month regular hopping exercise intervention can increase trabecular number and possibly trabecular volume fraction of the distal tibia. Our novel localised analysis demonstrated region-specific changes, predominantly in the anterior region, in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 51 publications
1
48
0
1
Order By: Relevance
“…Ellipsoid factor (EF) has been proposed as an alternative method to measure the plate-to-rod transition in trabecular bone [15]. EF has since been used within and beyond bone biology, for example in bone surgical implant testing [16] and the characterization of the trabecular bone phenotype of genetic dwarfism [17], of the primate mandible [18], of the human tibia [19], of animal models of osteoarthritis [20], and fuel cell performance [21,22]. Apart from the original critique of SMI [14], as far as we know, there have been no further reports of EF in osteoporotic samples in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ellipsoid factor (EF) has been proposed as an alternative method to measure the plate-to-rod transition in trabecular bone [15]. EF has since been used within and beyond bone biology, for example in bone surgical implant testing [16] and the characterization of the trabecular bone phenotype of genetic dwarfism [17], of the primate mandible [18], of the human tibia [19], of animal models of osteoarthritis [20], and fuel cell performance [21,22]. Apart from the original critique of SMI [14], as far as we know, there have been no further reports of EF in osteoporotic samples in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Participants who agreed to take part in the 6-month follow-up visit gave a written informed consent before participation. HR-pQCT (XtremeCT, Scanco Medical AG, Bruttisellen, Switzerland) scans of distal tibia were scheduled according to the manufacturer's standard protocol (60 kVp, 1000 mA, 100-msintegration time) at Month 0 and Month 6 [4] [28]. Prior to image acquisition, the tibia was lifted to a horizontal position, perpendicular to the gantry of the scanner to ensure the correct position upon entry.…”
Section: Participants and Hr-pqct Imagingmentioning
confidence: 99%
“…Nine cubic volumes of interest (VOIs) with a side length of 4 mm were extracted digitally from the trabecular region of distal tibia from nine participants. A 3D registration protocol, the same as in the previous publication [27] was used to ensure that VOIs from the same position were extracted from both the baseline and follow-up scans [4]. Briefly, a two-step registration was performed: first, the centres of mass were pre-aligned between two images; second, the pre-aligned follow-up image was registered to the baseline image based on a normalized mutual information metric and resampled using a Lanczos interpolator.…”
Section: Image Processing and Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that intensive mechanical stimulation results in thicker and mechanically stronger bones and bone morphology with individual elements of this bone tissue, trabeculae, aligned along the loading direction [1]. In contrast, a lack of mechanostimulation induces a bonemass reduction, thinning of trabeculae, and deterioration of mechanical properties [2]. Loadinduced adaptation is implemented through resorption of old and fractured bone and formation of a new bone material.…”
mentioning
confidence: 99%